High-performance work systems and individual performance: a longitudinal study of the differential roles of happiness and health well-being - Shi, Lulu; Van Veldhoven, Marc; Kooij, Dorien; Van De Voorde, Karina; Karanika-Murray, Maria (Frontiers in Psychology, 2024)
As a part of the growing strand of employee-centered HRM research, employee well-being is suggested to be a key mechanism that may help to explain the relationship between HRM and performance. To investigate how an employee’s well-being mediates the HRM-performance relationship, we distinguish between two types of well-being identified in prior work, happiness well-being and health well-being, and present arguments for differences in their effects on individual performance. Building on Job Demands-Resources (JDR) theory, we propose that happiness well-being positively mediates the relationship between perceived High-Performance Work Systems (HPWS) and individual task performance, while health well-being negatively mediates this focal relationship. Thus, happiness well-being fits the “mutual gains” perspective. In contrast, health well-being fits the “conflicting outcomes” perspective, and thus may be harmed by the HPWS to enhance the performance. We find partial support for our arguments in an analysis of longitudinal survey data of 420 participants spanning a total of four waves of data collection.